The Economic Efficiency Analysis of Digital Currency Markets - Salih M. Sahi (Genius Journals, 2022)
This work studies the influences of the first 10 digital currency markets. It utilized two main approaches. The first is inductive while the second is deductive. The latter starter from general to specific. Also, the first is theoretical and conceptual in structure and is the basic foundation for this research. This structure is examined and compared to empirical interpretations. This increased uncertainty period caused non-annualized every day stock returns of more than 5% with 10% returns and loses, respectively. The most digital currency one-half values were lost, yet 10% equity was disappeared due to COVID-19. Despite the rapid price decrease because of COVID-19, the digital currency markets have conserved their economic efficiency. The results have shown different fascinating insights facilitating understanding the influence of the crises on the investor’s behaviors. Yet, digital currency markets have retained their economic efficiency. Also, the initial concept showed with the beginning of volatility, investors aims at departing from traditional markets entering alternatives including the digital currency, at least in the early crisis stages
Keywords: Blockchain; Bitcoin; cryptocurrency; digital currency